Prevalence of Electronic Cigarette use in Al Kharj city - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: There is an alternative to smoking traditional tobacco cigarettes: electronic cigarettes, or e-cigarettes. The purpose of this study is to determine how common electronic cigarette use is among people in Al Kharj City. Materials and Methods: Between May and July of 2023, 570 people of both genders participated in a cross-sectional survey that was carried out in Al-Kharj, Saudi Arabia through a self-administered questionnaire. With 45.30% of the sample being male, the gender distribution showed a very balanced representation. In terms of educational attainment, 74.70% of participants held a university degree. Results and Discussion: The findings showed that 80.30% of the sample had never smoked regular cigarettes. The study participants’ e-cigarette consumption patterns showed that 78.20% had never used an e-cigarette. Significant differences were also seen in educational attainment, with greater education levels being associated with decreased e-cigarette use. In terms of quitting, the majority (81.40%) had never smoked regular cigarettes. E-cigarette users are more likely to be young adults and people who have used tobacco products in the past. Conclusion: These results should be considered by Saudi Arabian health-care professionals in their efforts to educate the public about the risks of e-cigarette usage.